2019
DOI: 10.1038/s41586-019-1115-5
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian ISWI and SWI/SNF selectively mediate binding of distinct transcription factors

Abstract: Chromatin remodeling complexes evict, slide, insert or replace nucleosomes, which represent an intrinsic barrier for access to DNA. Remodelers function in most aspects of genome utilization including transcription factor (TF) binding, DNA replication and repair1,2. While they are frequently mutated in cancer3, it remains largely unclear how the four mammalian remodeler families (SWI/SNF, ISWI, CHD and INO80) orchestrate the global organization of nucleosomes. To gain insight into this matter, we generated viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
211
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(234 citation statements)
references
References 35 publications
23
211
0
Order By: Relevance
“…Therefore, we analysed the contributions to NRL decrease caused by each of 8 chromatin remodellers that have been profiled in ESCs ( Fig 4B). We found that that Snf2h has a major role in this phenomenon, consistent with previous studies of Snf2H knockout in HeLa cells (66) and ESCs (39). In accord with the latter study, we observed that BRG1 has no detectable effect on NRL near CTCF, although it may be still involved in nucleosome positioning near TAD boundaries (67).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, we analysed the contributions to NRL decrease caused by each of 8 chromatin remodellers that have been profiled in ESCs ( Fig 4B). We found that that Snf2h has a major role in this phenomenon, consistent with previous studies of Snf2H knockout in HeLa cells (66) and ESCs (39). In accord with the latter study, we observed that BRG1 has no detectable effect on NRL near CTCF, although it may be still involved in nucleosome positioning near TAD boundaries (67).…”
Section: Discussionsupporting
confidence: 92%
“…Our analysis demonstrated that purely statistical positioning of nucleosomes near CTCF boundaries would result in a longer NRL than observed experimentally, and the effects of strong nucleosome-positioning DNA sequences, while compatible with the observed NRL, are limited to a small number of CTCF sites (38). A very recent study has investigated the effect of Snf2 and Brg1 remodellers on NRL in ESCs, suggesting Snf2 as the primary player (39). However, other factors may be at play as well.…”
Section: Introductionsupporting
confidence: 65%
“…Importantly, Dppa2 and Smarca5 proteins have been shown to physically interact in ESCs (Hernandez et al 2018), suggesting they may function together to regulate their ZGA target genes. Consistent with our overexpression results, analysis of recently published Smarca5 KO transcriptome data (Barisic et al 2019) revealed that loss of Smarca5 led to downregulation of ZGA transcripts ( Fig. 5D).…”
Section: Smarca5 Induces Zga-like Expression Via Dppa2supporting
confidence: 92%
“…We next investigated whether Smarca5 exerts its ZGA regulatory function through its catalytic ATPase activity or through interactions with accessory subunits of the ISWI complex. Analysis of published RNA-sequencing data of Smarca5 KO ESCs (Barisic et al 2019) revealed that wild-type, but not a catalytically-dead Smarca5 mutant, was able to restore expression of the 391 ZGA genes downregulated upon Smarca5 loss (Fig. 5D).…”
Section: Smarca5 Induces Zga-like Expression Via Dppa2mentioning
confidence: 99%
“…Transcription factors have been shown to intervene in several different ways in transcriptional processes in chromatin; quite generally they have been shown to compete with nucleosomes for binding to DNA [9][10][11][12] and they also interact with chromatin remodelers [13]. These interactions of transcription factors with the nucleosomes are essentially controlled by direct and indirect sequence specificities and otherwise dominated by steric exclusion effects and therefore have probably only little or no specific regulatory relevance for the initial recruitment of chromatin remodelers; they might, however, be important for the maintenance of transcriptionally active states.…”
mentioning
confidence: 99%